World Heritage and Climate Change Impacts and Adaptation - Bertolin, Chiara; Perry, Jim (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Natural World Heritage sites, such as the Serengeti, or Natural and Cultural Heritage sites, such as the Historic Centre of Rome, have the common feature of being a treasured resource of global importance. The 1121 properties on the World Heritage (WH) list have permanent recognized value for humankind. Most of those >1000 locations are at some risk from changes in climate. Globally, scholars and managers seek to understand current and future climatic stresses, mitigation and adaptation opportunities. There is a strong need for the "So What?" in World Heritage studies. The invited papers in this volume address natural, cultural and mixed WH sites, and each offers a fresh perspective on assessing the degree of risk from changing climate and guidance on acting to mitigate and adapt to climate changes to provide new awareness and tools to improve their state of conservation for the future.